The Triple Helix Model of Islamic Social Financial Institutions Achieves SDGs 2030 Finance in North Sumatra - Herlina, Sri; Barus, Dana Syahputra; Syahbudi, Muhammad (SAINTIS Publishing, 2025)
This research is planned to examine one of the development instruments used by Islamic economics, namely Islamic social financial institutions/philanthropy, namely OPZ, which is part of Islamic Social Finance. Historical evidence speaks to zakat as an important development instrument for the country. Zakat and the SDGs have significant relevance. This is because zakat is an instrument of Islamic economic development that places maqasid sharia as its implementation goal. Therefore, optimization of zakat on the most optimal SDGs indicators needs to be determined. The method in this research uses a type of qualitative analysis to determine which SDGs indicators need to be prioritized and supported by the Islamic Social Finance program in North Sumatra. The results obtained from the study indicate that the achievement of SDGs, especially in the aspect of sustainable economic empowerment in 2030, is not a utopian thing if there is synergy between all stakeholders for a better Indonesia. Based on the results of research conducted by Islamic financial institutions, Islam is quite good and certainly needs to be appreciated and supported by various parties, especially the role of the government in terms of regulation, protection, and institutional guarantees. Public awareness of the virtues of almsgiving, charity, waqf, and the obligation to pay zakat (alms) should be continuously nurtured and increased. Other Islamic financial institutions with similar visions and missions should continually evaluate their management and distribution to ensure they are targeted, effective, and sustainable.